IL-36RN gene: key insights into its role in pediatric pustular psoriasis pathogenesis and treatment - Wang, Ye; Li, Mingyue; Hou, Changcheng; Wang, Yueyue; Guo, Jing; Wang, Xurui (Frontiers in Pediatrics, 2025)
Pediatric pustular psoriasis (PPP) is an autoimmune skin disease that seriously affects the physical and mental health of children. The IL-36RN (Interleukin-36 Receptor Antagonist) gene plays a key role in the pathogenesis of PPP. This review comprehensively elaborates on the research progress of IL-36RN in the context of the pathogenesis and treatment of PPP, covering the basic structure, function, mutation sites and types, and inheritance patterns of the gene and its role in the pathogenesis of PPP. In addition, we discussed the frequency of IL-36RN mutations in patients with different types of PPP and the treatment methods for these patients, aiming to provide a valuable reference for further research and treatment of this disease.